Evaluation programs social responsibility in the Cerrejón mine (2014)
Due to the oil crisis of the 1970s new energy resources in the world were sought, La Guajira to have the largest reserves in Latin America plays a strategic role. This apartment is located in the north of the country. Coal mining by Cerrejón inception in 1985, becoming the mine to the world’s largest open pit. Since then, it has generated millions of dollars in revenue for the company but very little for Colombia and especially for the region, although this activity is the main economic source. Cerrejón is a world of contrasts in economic, social and environmental aspects and questions about whether born this activity is positive or negative and whether it has brought prosperity and quality of life for its citizens or otherwise has been detrimental to this region. Mining in the Cerrejón has generated advances and benefits to society but also impacts on the environment, on recent studies have been done, most negative result. The government has passed laws on mining, miners responsibility, environmental responsibility and punishment in such case is not met the regulations.